Validitas Media Pembelajaran Kimia Berbasis Augmented Reality (AR) Menggunakan Assemblr Edu pada Materi Hidrokarbon - Fatma Tahir; Astin Lukum; Masrid Pikoli; Lukman A.R. Laliyo; Akram La Kilo; Erga Kurniawati (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to determine the level of validity of Augmented Reality (AR)-based chemistry learning media using the Assemblr Edu platform on hydrocarbon material. This learning media was developed through the 4D development model (Define, Design, Develop, Disseminate). Validation was carried out by three experts using an instrument in the form of a validation media sheet that includes aspects of content, visual appearance, interactivity, and suitability with learning objectives. The validation results showed that the developed learning media obtained a validity score of 96.39% and was included in the "very valid" category. This shows that the media is suitable for use in the chemistry learning process at the high school level, especially on the topic of hydrocarbons. With AR technology, this media is expected to improve students' conceptual understanding visually and interactively. Based on the results of the study, it can be concluded that this media is effective and valid as a means of supporting innovative modern chemistry learning.